Granting and Renegotiating Infrastructure Concessions : Doing it Right - Guasch, J. Luis (Washington, DC: World Bank, 2013)
In most developing and industrial countries, infrastructure services have traditionally been provided by government enterprises, but in developing countries at least, these enterprises have often proven to be inefficient, unable to provide much-needed investments, and manipulated to achieve political objectives. By contrast, many studies have shown that over the past 30 years, private (or privatized) enterprises in developing countries have, on average, delivered superior performance and needed investments. Explanations differ on why this discrepancy exists. Private enterprises are driven by a desire for profits and may have more professional know-how in management, operating procedures, and use of appropriate technology. But perhaps the most important reason for their stronger performance is that privatization makes intervening in enterprise operations difficult for governments and politicians, so government manipulation is less likely. However, the issue, in general, has been how to ensure that the improved performance and efficiency gains are passed through to the users through lower tariffs and increased coverage, while allowing firms to earn a fair rate of return on their investments.